Property and power: lessons from Piketty and new insights from the HFCS - Miriam Rehm; Matthias Schnetzer (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
This paper argues that the cumulative causation processes between wealth and power risk leading to an escalation of wealth inequality. Piketty's historical description of this development from administrative data for individual countries is corroborated with new survey data for the eurozone, the Household Finance and Consumption Survey (HFCS). Wealth is extremely unequally distributed in the eurozone – much more so than income. Furthermore, we provide a multi-faceted picture of wealth distribution in Europe using the socio-economic characteristics available in the HFCS, and we show that inheritances are the single most important factor for wealth inequality. The structural power to shape economic and political institutions is thus ever more concentrated. Finally, we discuss three channels through which the unequal distribution of private assets may affect power relations and economic activity.
Keywords: D31; E12; P16; 330; wealth inequality; power; Piketty; Household Finance and Consumption Survey